Padronização para avaliação rápida da qualidade de sementes florestais pelo teste de tetrazólio - Teração, Bruna Santos (Universidade Federal de São Carlos, 2021)
The potential of using the tetrazolium test for rapid evaluation of seed lots of native forest species, highlights the need for protocols for its application in forest species. In this work, we sought to analyze the efficiency of the tetrazolium test as a technology to provide fast and safe information about the quality of seeds. For the tests, the seeds of Senna macranthera and Senegalia polyphylla, both with physical dormancy, after scarification, and the Handroanthus chrysotrichus, were submitted to three times of solution of 2, 3, 5 triphenyl tetrazolium chloride (0.075; 0, 5 and 1%), for different immersion times at 40 ° C. Each seed was analyzed and classified, in three vigor classes, according to the presence, extent and position of stains. The seeds of H. chrysotrichus obtained color in the three practices, but only in 0.5 and 0.075% there was no statistical difference with the germination test. The seeds of S. macranthera and S. polyphylla obtained an adequate color only in the recommendations of 0.5 and 1%. It is recommended to adopt a concentration of 1% for 20 hours for seeds of S. macranthera or 0.5% for 24 hours, if time is not a limiting factor. For S. polyphylla, the most suitable concentration was 0.5%, for 6 hours, as it uses a lower amount of tetrazolium salt, reducing its cost. And in the case of H. chrysotrichus, with direct immersion of the seeds in the tetrazolium solution, a concentration of 0.5% for 6 hours or 0.075% for 12 hours is recommended.
Standardization for rapid evaluation of the quality of forest seeds by the tetrazolium test.
Keywords: Viabilidade; Análise de sementes; coloração; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::FISIOLOGIA DE PLANTAS CULTIVADAS